The Russian Orthodox Church in the occupied territories of the Caucasus in August 1942 — February 1943 - Shishkin Evgenii, priest (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The status and activities of the Russian Orthodox Church in the 1942-1943 is analysed on the material of the North Caucasus and the Kuban. Battle for the Caucasus and the Battle of Stalingrad — the crucial events of the World War II — were accompanied by the fi rst phase of the occupation of a large part of the South of Russia. We study both positive and tragic facets of church life in the occupied territories of the enemy. The process of spontaneous legalization of the clergy and parish communities, the Soviet government outlawed in the preceding period, traced the fate of the Orthodox pastors and churches — returning to serve and die at the hands of the Nazis, open to the service and destroyed by Hitler’s army. The internal problems of religious policy of the German Headquarters and especially its implementation in the region, as well as hierarchical and jurisdictional problems caused by the Renovationist schism, and their perspective in conditions of military everyday are examined. Marked combining processes in the church community and the formation at the local level prerequisites for overcoming the disunions ecclesiastic of the 1920s — 1930s.